Apoptosis in Acanthamoeba castellanii belonging to the T4 genotype. (3rd May 2017) - Baig, Abdul M.; Lalani, Salima; Khan, Naveed A.
Abstract : Here we describe features of apoptosis in unicellular Acanthamoeba castellanii belonging to the T4 genotype. When exposed to apoptosis‐inducing compounds such as doxorubicin, A. castellanii trophozoites exhibited cell shrinkage and membrane blebbing as observed microscopically, DNA fragmentation using agarose gel electrophoresis, and phosphatidylserine (PS) externalization using annexin V immunostaining. Overall, these findings suggest the existence of apoptosis in A. castellanii possibly mediated by intrinsic apoptotic cascade. Further research in this field could provide avenues to selectively induce apoptosis in A. castellanii by triggering intrinsic apoptotic cascade.